Prevention and Annulment of Marriage According to the Civil Code and Law No. 1 of 1974 - Ali Ansori; Fahriani Tanjung; Mia Kresni Indah Sari; Sulistia Putri; Varissa Rikaz Putri (ISNU Sumatera Utara, 2025)
This study examines the prevention and annulment of marriages according to the Civil Code (KUHPerdata BW) and Law No. 1 of 1974 concerning Marriage in Indonesia. The background of this study is the importance of understanding the legal basis governing the validity of marriages to maintain social order and protect individual rights. The differences between these two legal systems create complexity in their application in society, particularly regarding the reasons underlying the prevention and annulment of marriages. The study aims to analyze the comparative legal regulations between the Civil Code (KUHPerdata BW), which has colonial nuances, and Law No. 1 of 1974, which is based on national legal principles. This study is useful for the development of legal science, especially in understanding the implementation of marriage law that is relevant to the context of Indonesian society. The method used is library research by reviewing legal literature, laws and regulations, and related documents. Case studies are used to strengthen the analysis, by highlighting legal cases that reflect the challenges of implementing these rules in the field. The results of this study are expected to contribute to the development of marriage law policies that are more inclusive, harmonious, and in accordance with the needs of society and current developments.